Residential satisfaction within selected public housing estates in Lokoja Kogi State, Nigeria - Saliu, Hassan Ozovehe; Sagada, Musa Lawal; Maina, Joy Joshua; Sani, Maruf (Penerbit Universiti Kebangsaan Malaysia, 2023)
Residential satisfaction has been assessed by various authors, who reported varying degrees of dissatisfaction and satisfaction. However, the differences in satisfaction among the various housing components remain an issue. The study investigates residential satisfaction in specific housing estates in Lokoja, Kogi State, aiming to understand the various aspects that contribute to satisfaction. The research collected responses from 215 residents and employed statistical analysis using SPSS version 21. Among the four housing sub-components examined, satisfaction levels varied. Housing unit attributes had the lowest satisfaction level, indicating poor satisfaction. Housing socio-economic attributes, housing neighbourhood attributes, and housing management attributes showed moderate satisfaction levels. Significantly different satisfaction levels were found among these sub-components, as demonstrated by the Kruskal-Wallis test outcomes. Satisfaction with housing unit attributes, socio-economic attributes, and neighbourhood attributes were all statistically significant. Interestingly, satisfaction with the management attribute was not statistically significant due to high resident involvement in housing management. The study suggests revising government policies regarding public housing estates and emphasizes resident involvement throughout the housing process to enhance satisfaction across all sub-components. These findings have implications for housing policies, urban planning, and resource allocation, striving for more inclusive and satisfying living conditions. The study's outcomes could influence housing development approaches, ultimately improving the overall quality of life in Lokoja, Kogi State.